Integration of Hypergeometric Supertrigonometric Functions Using Generalized Hypergeometric Functions and its Applications - Basnet, Ganesh Bahadur; Pahari, Narayan Prasad; Paudel, Resham Prasad (Journal of Institute of Science and Technology, 2025)
This study explores the integration of hypergeometric supertrigonometric functions, with a particular focus on hypergeometric supersine and hypergeometric supercosine functions, by leveraging the properties and relationships of generalized hypergeometric functions. By expressing hypergeometric supertrigonometric functions in terms of hypergeometric functions, we derive integral representations that connect these functions to classical results in generalized hypergeometric theory. The work emphasizes the role of convergence conditions, parameters and highlighting special cases where the results can be expressed in simple form, providing a unified framework for evaluating integrals involving hypergeometric trigonometric functions.